Regioselective Michael Addition of Anthrone to Methyleneindolinones - Zhao, Huaili; Wang, Xiaoxiao; Wang, Liang; Xiao, Jian (Synthesis, 2016)
Regioselective Michael addition of anthrone to methyleneindolinones catalyzed by Et3N was developed. The reaction furnished structurally interesting hybrid derivatives of oxindoles and anthrones in high yield, high regioselectivity, and high diastereoselectivity. Electronic effects had a dramatic influence on both the regioselectivity and diastereoselectivity, which could be finely tuned by changing the substituents on the methyleneindolinones.
Keywords: Michael addition; anthrone; methyleneindolinone; electronic effects; regioselectivity